MUTU KIMIAWI TERASI DENGAN FORMULASI UDANG REBON (Acetes sp) DAN IKAN RUCAH YANG BERBEDA - Nabila Ukhty; Anhar Rozi; Andiani Sartiwi (Universitas Teuku Umar, 2017)
Terasi is a product of fermentation-based on rebon or fish with the addition of salt. Fermentation with salt led to an overhaul of proteins into amino acids eg glutamic acid as a producer of distinctive taste shrimp paste. Raw material, salt concentration and fermentation time is an important factor in the process of making paste. This study aimed to analyze the effect of different formulations of rebon (Acetes sp) and HTS generated against chemical quality paste. Raw materials used in this study is rebon (Acetes sp.) and fish HTS. Treatment used is the difference rebon formulation composition of fish and meat. Research methods using the experimental method with descriptive design field. Parameters tested include moisture content, ash content, fat content, protein, carbohydrates, pH, and glutamic acid. Based on the results obtained paste with the best formulation of the paste P1 treatment with a water content of 15.48%, 39.52% ash content, the fat content of 7.23%, 42.50% protein content, carbohydrate content of 4.73%, pH 5 , 67%, and 22.56% glutamic acid.